Solution-processed diarylfluorene derivatives for violet-blue amplified spontaneous emission and electroluminescence. Issue 38 (18th September 2017) - Han, Ya-Min; Bai, Lu-Bing; Yin, Cheng-Rong; Ou, Chang-Jin; Zhang, Xin-Wen; Zuo, Zong-Yan; Liu, Bin; Yu, Meng-Na; Lin, Jin-Yi; Zhao, Jian-Feng; Zhu, Wen-Sai; Liu, Yu-Yu; et al.
Abstract : A series of solution-processable 4-subsituted diarylfluorene small molecules for violet-blue amplified spontaneous emission and electroluminescence. Abstract : A series of solution-processable diarylfluorene-based materials with pendent 4-(hexyloxy carbazole)-9, 9-diphenyl-9 H -fluorene (MC6 Cz) or 4-(octyloxy)-9, 9-diphenyl-9 H -fluorene (MC8 ) as the core and endcapped with different charge transport moieties such as phenylcarbazole (NPC) or triphenylemine (TPA) have been synthesized and investigated systemically. These materials exhibited bright fluorescence emission from violet-blue to deep blue without molecular aggregation in diluted solutions and films. Furthermore, these materials also displayed prominent virtues including superior solution-processability and amorphous characteristics. Consequently, the EL spectra of the solution-processed organic light-emitting diodes (OLEDs) are expected to be similar to the corresponding PL spectra, suggesting intramolecular photophysical behavior. MC6 Cz-9-NPC as an emitting layer presented the highest maximum luminance of about 1560 cd m −2 with a lower turn on voltage of 3.5 V. In contrast, the ASE results revealed that the MC8 core-containing compounds exhibited relatively lower thresholds comparable with traditional conjugated or star type polymers, which could be promising optical gain media. We proposed a novel molecular design strategy to construct high-performance solution-processed violet-blue fluorophores.